COVID‐19 death and kidney disease in a multiracial Asian country. Issue 7 (7th May 2022) - Goh, Bak Leong; Shanmuganathan, Malini; Peariasamy, Kalaiarasu; Misnan, Nor Arisah; Chidambaram, Suresh Kumar; Wong, Eddie Fook Sem; Pathmanathan, Mohan Dass; Ang, Kim Liong; Wong, Hin Seng; Yeap, Lena Lay Ling
Abstract: Introduction: COVID‐19 infection and kidney disease (KD) carry a considerable risk of mortality. Understanding predictors of death and KD may help improve management and patient outcome. Methods: This is a prospective multicentre observational study conducted in a multiracial Asian country to identify predictors of death and acute kidney injury (AKI) in hospitalized COVID‐19 patients from January to June 2020. Results: A total of 6078 patients were included in this study. Mean age was 37.3 (±16.8) years, 71% were male, 59.4% Malay, 6.7% Chinese, 2.3% Indian and 31.7% other ethnicities. AKI was seen in 3.5% of patients while 1.6% had pre‐existing chronic kidney disease (CKD). Overall case fatality rate (CFR) was 1.3%. Patients with KD (AKI and CKD) had CFR of 20%. Many factors were associated with increased risk of death and AKI. However, significant predictors of death after adjustment for covariates were age (>70 years), Chinese ethnicity, diabetes mellitus (DM) and KD. Adjusted predictors of AKI were age (>51 years), DM and severity at presentation. Chinese were 2.58 times more likely to die ( p = .036) compared to Malay. Centre capacity to manage, ventilate and dialyze patients significantly influenced death. Among those with AKI, the most common symptoms were fever, cough, and dyspnea. They had lower absolute lymphocyte count, were more likely to be admitted to ICU, required more ventilation and longer hospitalization. Conclusion: Patient and centre factors influence death and AKI among COVID‐19 patients. This study also demonstrates death disparities across different racial groups and centre capacities in this multiracial Asian country. SUMMARY AT A GLANCE: This study found that COVID‐19 has disproportionately impacted vulnerable populations: elderly, those with kidney disease, diabetes, and certain ethnic group. There were also death discrepancies in centre's capacity to manage, ventilate and dialyze patients.